Husband's Support for Pregnant Women's Unwillingness with Covid-19 Vaccination - Frisca Desma Ayu Kusuma Wardani; Stella Maris Bakara; Suminah Suminah (Sarana Ilmu Indonesia (salnesia), 2023)
The development of Covid-19 cases shows that the number of confirmed cases of pregnant women with Covid-19 in serious condition has increased in several large cities in Indonesia. This study aimed to explore the correlation between husband's support and pregnant women's disapproval of Covid-19 vaccination. This research used analytical methods with a cross sectional design. Data was collected between October 14 and November 14 2022 in the Piyeung Community Health Center working area. All pregnant women in the area became the research population, and 85 people were taken as samples using the total sampling method. The research instrument consists of primary data collected through questionnaires and secondary data obtained from the Covid-19 Vaccination Achievement Report for Pregnant Women at the Aceh Besar Health Service and Piyeung Community Health Center. Data analysis involves univariate analysis techniques to distribute variable frequencies, as well as bivariate analysis using the chi-square test to assess the relationship between independent and dependent variables. The results of the univariate analysis showed that the majority of subjects (73 people or 85.9%) were not willing to be vaccinated. The research results showed that there was a significant correlation between husband's support (p-value=0,000) and pregnant women's unwillingness to be vaccinated against Covid-19. Therefore, it is hoped that health workers will be more proactive in promoting Covid-19 vaccination to pregnant women and provide the necessary information to increase awareness and acceptance of this vaccination.